Effect of Continuous Working Fluid Flow Direction on Power Generation from Piezoelectric Sensors - Elin Yusibani; Farah Dina; Cut Khairunnisa; Fashbir Fashbir; Muhammad Syukri Surbakti; Bambang Joko Suroto (Universitas Ahmad Dahlan, 2022)
This paper presents an experimental study to support the concept of generating energy by a continuous flow of water using piezoelectric sensors. This study is aimed to determine the effect of external force direction of continuous water flow, i.e., vertical and horizontal, on the output of the piezoelectric sensors. The piezoelectric type of ABT-441-RC is used and arranged in parallel. IC MAX471 as an amplifier and Arduino Uno R3 to read the flow rate, voltage, and current were employed. Flow rates with variations of 0.00011 up to 0.00030 m3/s are set to study the voltage and current of the output. The numbers of piezoelectric sensors used are 4, 6, 8, and 20. As a result, it is found that the pressure in the vertical direction differs up to 68% from the pressure in the horizontal one. The voltage and current in the vertical direction, compared to that of the horizontal direction, differ as much as 85% at a low flow rate and decrease down to 63% at a high flow rate for voltage and 86% to 34% at a low to high flow rate for current. In conclusion, the current generation by the present arrangement is within the micro-ampere range, and the voltage is in a volt range, respectively.